Representation of Local Wisdom in the Character of Mahar in the Film Laskar Pelangi: The Context of Arts Education - Trisnawati, Eky; Agustin, Kurnia Dwi Marandtika (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
This study analyzes the representation of local wisdom-based art education through the character Mahar in the film Laskar Pelangi (The Rainbow Troops). Mahar, who shows a strong inclination towards art and traditional music, functions as a vital cultural symbol within the Belitung Malay community. The research uses a qualitative descriptive method with an intrinsic approach to explore the implicit cultural representations. Data were gathered via key scene observation, dialogue, and visual elements. Source triangulation and limited member checking ensured data trustworthiness. Findings show that Mahar represents local wisdom primarily through the use of the rebana (traditional frame drum) and the song "Bunga Seroja". The rebana symbolizes the community’s cultural and spiritual identity and strengthens social cohesion. The Malay song "Bunga Seroja" symbolizes the fighting spirit and reinforces camaraderie. This representation asserts that local wisdom-based art education, as embodied by Mahar, offers a solution for strengthening students’ cultural identity against globalization. The study addresses a gap in previous research which focused heavily on the film’s socio-economic aspects, overlooking the local art and cultural values championed by its characters.